Evaluación del desempeño del estándar 802.11ad (60 GHz) para enlaces de backbone para distancias cortas en ambientes con LOS (línea de vista). - Loarte Caraguay, Robert Iván (2023)
Wireless networks have been of great help to connect areas of difficult access, as well as to offer wireless connectivity to the large number of devices that exist today, such as cell phones, game consoles, IoT devices and voice assistants. Currently there are great advances in the technological field, taking into account this, in telecommunications networks every day new connection methods and standards emerge to facilitate access to data and Internet. In this sense, the millimeter waves that work in the 60 GHz band, found in the 802.11ad standard, allow the transfer of a large amount of information wirelessly, when there is line of sight and it is at a short distance, depending on the technical specifications of the hardware to be used. Based on this, the objective of this TT is to analyze the technology currently available in the market as brands, antenna types, technical details of equipment for point to point links that are available in the country. We will choose the equipment that will allow us to perform a point to point link at a certain distance and perform link tests such as latency, up/down traffic and processing capacity. The installation of this equipment will be done in open environmental settings that will allow us to evaluate the performance and link capacity when there is interference due to rain, because millimeter waves by their nature are very susceptible to interference by this type of phenomena. Keywords: Wireless communications, Data networks, Millimeter waves, 60 GHz